Penggunaan Media Pembelajaran Animasi Terhadap Hasil Belajar Subtema Manusia Dan Lingkungan - Lina Novita; Entis Sutisna; Khansa Rohadatul’Aisy Rabbani (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
The background of this research was a lack of learning outcomes of human and environmental sub-themes. The purpose of this research was to increase the effectiveness of learning outcomes using animation-learning media (experimental class) and without media (control class) on the human and environmental sub-theme in fifth grade. The subjects of this research were 5th grade, totaling 74 students. The analysis technique used the analysis prerequisite test that included the normality test, homogeneity test, and hypothesis test with the t-test. The results of this research showed that there was a significant difference in the mean N-gain values of the learning outcomes of the experimental class and the control class. The average score of N-gain in the experimental class was 74 with a mastery of learning outcomes 97, 29%, while the average score of N-gain in the control class was 64 with a mastery of learning outcomes 81, 08%. The results of the calculation statistical hypothesis test that showed t value (3, 25) was higher than t table (2, 000) with dk 72, and the significant formula α = 0, 05, from these results showed that Ho is rejected and Ha was accepted. Based on the results of this research, it can be concluded that there was an influence of the use of animated learning media on the learning outcomes of the sub-theme of humans and the environment in fifth grade at elementary school.